Idosos cuidadores de idosos em arranjos familiares com e sem a presença de crianças : sobrecarga, otimismo e estratégias de enfrentamento - Oliveira, Nathalia Alves de (Universidade Federal de São Carlos, 2016)
Changes in socio-cultural profiles added to increasing number in the elderly population have favored the formation of new family compositions in the presence of elderly and children. In this context the elderly has become known for taking care for other elderly and children. This new configuration that has the elderly protagonist can take to an excess of competing demands and induce burden, on contrary, the child's presence can increase positive feelings such as optimism and assist in the choice of coping strategies. This study aimed to compare the level of burden, optimism and coping strategies of elderly caregivers of elderly residing with and without the presence of children. The study was based on the quantitative method of research and all ethical guidelines were followed. There were interviewed 301caregivers elderly registered in the Family Health Units in a municipality in São Paulo state. The instruments used were: Scale independence in activities of daily living Katz; Scale of instrumental activities of daily living Lawton; Socio-demographic characterization of the child; Sociodemographic and of care of elderly receivers care, sociodemographic and health conditions of the elderly caregiver, Zarit Burden Intervew, Pinto Spirituality Scale and Pais-Ribeiro and Inventory to assess coping strategies. For data analysis elderly caregivers were divided into two groups G1 (residing without children) and G2 (living with children). The results show that most of the children were male (52.6%) with a mean age of six. Among elderly caregivers in both groups there was prevalence of woman (G1 = 74.3%; G2 = 81.8%), the median age in G1 was 69 years and 65.5 years in G2. Among the elderly care recepients, most were male (66.9% G1 = G2 = 77.3%) with a median age of 73 years in G1 and 69 years in G2. Elderly caregivers in G2 showed significantly higher level of burden compared to G1 (p = 0.01). The level optimism was high for both groups and there were no significant differences between them. In the analysis of coping strategies elderly caregivers in G1 reported using more focused strategies in the expression of negative emotions (p <0.01), religiosity (p = 0.01) and inhibition of negative emotions (p = 0.01) compared to G2. The results reveal important data that contribute the valiation of the elderly caregiver in an intergenerational context and can support the planning of interventions for caregivers in primary care settings.
Elderly caregivers of elderly in family arrangements with and without the presence of children: Burden, optimism and coping strategies.
Keywords: Idoso; Criança; Cuidadores; Gerontologia; Age; Child; Caregivers; Gerontology; CIENCIAS BIOLOGICAS; CIENCIAS DA SAUDE::ENFERMAGEM